Caudal Regression Syndrome: Case Report - Ariza Echavarria, Dayana; Del Toro Trillos, Carlos; Paez Jimenez, Daniela; Salcedo Brand, Juan (Revista Argentina de Neurocirugía, 2024)
We present the clinical case of a 2-year-old patient with Caudal Regression Syndrome, a rare congenital malformation affecting the caudal region. The diagnosis was based on urinary tract manifestations and findings observed in the emergency department's urinary tract ultrasound, which led to the performance of a tomography revealing absense of sacral and coccygeal bodies. The patient received multidisciplinary management and was discharged for outpatient follow-up. This case highlights the mode of presentation of Caudal Regression Syndrome without prenatal diagnosis through manifestations in the gastrointestinal or urinary tract.
Keywords: Caudal regression; congenital anomalies; gestational diabetes; lumbosacral malformation